The human body - Fullick, Ann, 1956- (Des Plaines, Ill. : Hienemann Library, 1999)
Looks at various aspects of the human body, including the skeleton, muscles, digestive system, reproductive organs, and more.
Includes bibliographical references (p. 31) and index.
Appraisal-Science Books for Young People.
L.A. Recommended Foreign Language.
5.9.
5.9
3-6
Keywords: Human body -- Juvenile literature; Human physiology -- Juvenile literature; Human anatomy; Human body; Human physiology; Human body; Physiology